2020
DOI: 10.2174/1573406415666181203114629
|View full text |Cite
|
Sign up to set email alerts
|

The Substantial Improvement of Amphotericin B Selective Toxicity Upon Modification of Mycosamine with Bulky Substituents

Abstract: Background: It is assumed that the unfavorable selective toxicity of an antifungal drug Amphotericin B (AmB) can be improved upon chemical modification of the antibiotic molecule. Objective: The aim of this study was verification of the hypothesis that introduction of bulky substituents at the amino sugar moiety of the antibiotic may result in diminishment of mammalian in vitro toxicity of thus prepared AmB derivatives. Methods: Twenty-eight derivatives of AmB were obtained upon chemical modification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It was found that AmB at concentrations about an order of magnitude higher than MIC, self-associate to form dimers or higher oligomers, that are equally toxic to mammalian and fungal cells, whereas AmB monomers, dominating at concentrations close to MIC, are selectively fungicidal [ 9 ]. Several attempts have been made to improve selective toxicity of AmB by its chemical modifications, mainly at the amino group of mycosamine or the carboxyl functionality, resulting in disturbance of self-association ability [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that AmB at concentrations about an order of magnitude higher than MIC, self-associate to form dimers or higher oligomers, that are equally toxic to mammalian and fungal cells, whereas AmB monomers, dominating at concentrations close to MIC, are selectively fungicidal [ 9 ]. Several attempts have been made to improve selective toxicity of AmB by its chemical modifications, mainly at the amino group of mycosamine or the carboxyl functionality, resulting in disturbance of self-association ability [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modification on the mycosamine nitrogen leads to less toxic amphotericin B derivatives without adversely affecting the activity. [ 26 ] Thus, it was reasoned that conjugation of amphothericin B to glycogold nanoparticles via the amine group may reduce the toxicity of the drug. The carboxylic acid moieties on the nanoparticles will impart charge to the conjugate and allow for more water molecules to interact with the nanoparticle for better aqueous dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, new methods to cure this disease have been proposed, including host-directed and combinational therapies, drug repurposing and nanotechnology. In addition, ionic liquids, other solvents and nanoparticles [ 18 , 19 , 56 ] have also played a role in what concerns the increase in drug solubilization and the improvement of formulations and delivery [ 17 , 57 ]. Thus, the search for organic salts or ionic liquids as a novel method for easy transformation of amphotericin B in high yields without additional protection/deprotection steps seems desirable to investigate.…”
Section: Introductionmentioning
confidence: 99%